2008
DOI: 10.1371/journal.pone.0001708
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Signatures and Functional Properties of Anti-Human CD28 Superagonistic Antibodies

Abstract: Superagonistic CD28 antibodies (CD28SAs) activate T lymphocytes without concomitant perturbation of the TCR/CD3-complex. In rodents these reagents induce the preferential expansion of regulatory T cells and can be used for the treatment of autoimmune diseases. Unexpectedly, the humanized CD28 superagonist TGN1412 caused severe and life threatening adverse effects during a recently conducted phase I clinical trail. The underlying molecular mechanisms are as yet unclear. We show that TGN1412 as well as the comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 45 publications
4
91
0
Order By: Relevance
“…31 Concerning TGN1412, whereas binding affinity for CD28 was similar between cynomolgus macaques and humans, 21,32,33 PBMC from macaques were not stimulated in vitro by immobilized TGN1412, contrary to results with human cells. 24,34 It was first suggested that the differences could be due to the loss of Siglecs inhibitory molecules during human evolution, 35 but Richard Stebbings group later reported that CD4 + effector memory T cells were the predominant source of cytokine release after TGN1412 infusion, and that macaque CD4 + T cells, but not human counterparts, lose CD28 expression during their differentiation into memory cells. 20 Whereas it is now obvious that cynomolgus or rhesus macaques cannot constitute relevant species for preclinical immunotoxicity evaluation of emerging drugs targeting CD28, these animals still continue to be used for that purpose.…”
Section: Mabs Volume 6 Issuementioning
confidence: 99%
“…31 Concerning TGN1412, whereas binding affinity for CD28 was similar between cynomolgus macaques and humans, 21,32,33 PBMC from macaques were not stimulated in vitro by immobilized TGN1412, contrary to results with human cells. 24,34 It was first suggested that the differences could be due to the loss of Siglecs inhibitory molecules during human evolution, 35 but Richard Stebbings group later reported that CD4 + effector memory T cells were the predominant source of cytokine release after TGN1412 infusion, and that macaque CD4 + T cells, but not human counterparts, lose CD28 expression during their differentiation into memory cells. 20 Whereas it is now obvious that cynomolgus or rhesus macaques cannot constitute relevant species for preclinical immunotoxicity evaluation of emerging drugs targeting CD28, these animals still continue to be used for that purpose.…”
Section: Mabs Volume 6 Issuementioning
confidence: 99%
“…Calcium measurements and fluorescence-activated cell sorting analyses Basically, calcium flux analyses in human T cells 19 as well as immunophenotyping by flow cytometry 7 were performed as described previously. Further details of these methods including complementation analyses in Itk knockout mice 20 and antibody descriptions are provided as supplementary data.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…In a phase I clinical trial the superagonist anti-CD28 monoclonal antibody TGN1412 induced a massive cytokine storm in human recipients, resulting in multiorgan failure in 6 healthy volunteers at 1/500th the dose that appeared safe in mice and nonhuman primates (44). Subsequent investigation demonstrated that superagonist activation of CD28 leads to a sustained calcium influx in human T cells, but not cynomolgus or rhesus monkey T cells (45). Human T cells also proliferate more vigorously after TCR activation than do T cells from chimpanzees, and this difference has been attributed to loss of inhibitory Siglec expression during human evolution (46).…”
Section: Figurementioning
confidence: 99%